FAKTOR - FAKTOR YANG MEMPENGARUHI NIAT PEMBELIAN ULANG KONSUMEN TERHADAP PRODUK PASTA GIGI - Antonius Satria Hadi (Jurnal Bisnis Darmajaya, 2019)
This study aims to determine the factors that influence the intention to repurchase toothpaste. These factors are product attributes, promotion mix, distribution channels and prices both partially and simultaneously. This study proposes two hypotheses. Data were collected from 99 respondents which got from questionnaire distributed to graduate degree students of Sanata Dharma University. The sampling technique uses non probability sampling. Based on data collection, this analysis uses multiple regression techniques, F test, and t test using Statistical Package for Social Sciences (SPSS) Version 17 software. The results showed that product attributes, promotion mix, distribution channels and prices had a positive and significant influence on consumers' repurchase intention on Pepsodent toothpaste. Each of hypothesis discussed detailly into this articleKeywords — product attributes, promotion mix, distribution channels, prices, repurchase intention